The use of "scratch and challenge board" as an alternative assessment tool to enhance university students' skills / Tajularipin Sulaiman ...[et al.] - Sulaiman, Tajularipin; Abdul Rahim, Suzieleez Syrene; Wong, KaiYan; Wan Jaafar, Wan Marzuki (Universiti Teknologi MARA, 2021)
In the teaching and learning process, assessment can be applied in various ways. In order to ensure the quality of education, assessment should be performed as a platform to support student learning. The role of assessment also ensures that students' learning outcomes meet the needs of the 21st century skills. "Scratch & Challenge Board" (SCB) can be used to support the 21st century teaching and learning environment through focus group discussions. Therefore, the aim of this study was to explore the perspectives of university students on the use of "Scratch & Challenge Board" as an alternative assessment tool in enhancing students' skills. This study applied the qualitative research approach. Data were collected through focus group interviews and related documents such as students' assignments. A total of 10 focus group were obtained, with 3-4 students in each group, and each discussion was moderated by an experienced moderator. Collected data were analysed using constant comparative data analysis methods to obtain the themes. Four (4) themes emerged in this study: (i) alternative assessment encourages active participation in learning, (ii) integrating technologies in assessment tools, (iii) relevant with 21st century skills, and (iv) improvement in learning environment. In conclusion, the "Scratch and Challenge Board" is an assessment tool that not only supports face-to-face teaching and learning, but can also be integrated with technological devices and social media platforms. The "Scratch and Challenge Board" also enhances students' 21st century skills